2019
DOI: 10.1249/mss.0000000000002234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperoxia on Critical Power and V˙O2 Kinetics during Upright Cycling

Abstract: Introduction/Purpose: Critical power (CP) is a fundamental parameter defining highintensity exercise tolerance, however its physiological determinants are incompletely understood. The present study determined the impact of hyperoxia on CP, the time constant of phase II pulmonary oxygen uptake kinetics (! O2), and muscle oxygenation (assessed by near-infrared spectroscopy) in 9 healthy men performing upright cycle ergometry. Methods: CP was determined in normoxia and hyperoxia (fraction of inspired O 2 = 0.5) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…Furthermore, it has been mentioned that ATP was responsible for a part of the muscle vasodilation that followed muscle hyperemia during exercise [ 35 ]. On the other hand, we can relate our results to other reasons, probably attributable to the increase in microvascular and intracellular oxygenation during exercise when compared to normoxia [ 36 , 37 ]. In addition, Goulding et al [ 36 ] demonstrated an increase in the concentration of muscle oxyhemoglobin under the condition of hyperoxia, which is an important physiological determinant for increasing exercise extension and tolerance.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, it has been mentioned that ATP was responsible for a part of the muscle vasodilation that followed muscle hyperemia during exercise [ 35 ]. On the other hand, we can relate our results to other reasons, probably attributable to the increase in microvascular and intracellular oxygenation during exercise when compared to normoxia [ 36 , 37 ]. In addition, Goulding et al [ 36 ] demonstrated an increase in the concentration of muscle oxyhemoglobin under the condition of hyperoxia, which is an important physiological determinant for increasing exercise extension and tolerance.…”
Section: Discussionmentioning
confidence: 83%
“…The data presented in the present study comprise retrospective analysis of data from five previous reports (Goulding et al 2017 , 2018a , b , 2019a , b ). A total of 26 participants completed the upright exercise experiments (Goulding et al 2017 , 2018a , 2019b ) and a total of 16 participants completed the supine exercise experiments (Goulding et al 2018b , 2019a ).…”
Section: Methodsmentioning
confidence: 99%
“…The data presented in the present study comprise retrospective analysis of data from five previous reports (Goulding et al 2017 , 2018a , b , 2019a , b ). A total of 26 participants completed the upright exercise experiments (Goulding et al 2017 , 2018a , 2019b ) and a total of 16 participants completed the supine exercise experiments (Goulding et al 2018b , 2019a ). However, several participants completed more than one of the original experiments, therefore in these instances only the data from the first experiment that the participant took part in was used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Priming exercise has the capacity to enhance both muscle O2 delivery and utilization at the onset of exercise (22,32,39). In Part 2, the effect of priming exercise on critical power could therefore have been via an independent effect of enhanced O2 availability, rather than a reduced ̇O2 per se (28). However, the reduction in τ[HHb+Mb (i.e.…”
Section: Oxygen Uptake Kinetics and Exercise Tolerancementioning
confidence: 98%
“…Despite the importance of critical power in determining exercise tolerance, its physiological antecedents have previously remained poorly understood. However, data from our laboratory has shown in healthy individuals that critical power, and by extension exercise tolerance, is determined by the rate of increase in pulmonary oxygen uptake (̇O2, a proxy for muscle ̇O 2 kinetics, 26) at the onset of exercise (24)(25)(26)(27)(28), specifically the fundamental phase time constant (̇O2).…”
Section: Introductionmentioning
confidence: 99%